Analisis Kesyariahan Kartu Kredit Bank Syariah Indonesia Sebagai Media Transaksi Non Tunai. - Maulidatul Islami; Atika Zahra Maulida (Islamic Economics and Business Faculty of UIN Antasari, 2022)
The purpose of this study was to determine whether the credit card product issued by Bank Syariah Indonesia, namely the Hasanah Card , was in accordance with and actually implemented the Sharia Card as stipulated in the DSN-MUI fatwa No. 54/DSN-MUI/X/2006. The research method is a qualitative research using a descriptive approach to describe sharia principles in the hasanah card. data were collected by the field research (field research) with primary sources obtained from sources in the form of interviews and observations and library research (library research) with socio legal research. The results of this study are the application of sharia principles to the Hasanah Card product by Bank Syariah Indonesia is still not in accordance with the DSN-MUI Fatwa No. 54 of 2006. This can be seen from the DSN MUI fatwa regarding tadwidh provisions, usage limits to reduce consumptive behavior, and transaction provisions at non-halal merchants that are not yet fully implemented in the hasanah card practice. Tujuan dari penelitian ini adalah untuk mengetahui apakah produk kartu kredit yang dikeluarkan oleh Bank Syariah Indonesia yaitu Hasanah Card sudah sesuai dan benar-benar menerapkan prinsip Syariah Card yang diatur dalam fatwa DSN-MUI No.54/DSN-MUI/X/2006. Metode penelitian adalah penelitian kualitatif dengan menggunakan pendekatan deskriptif untuk menggambarkan prinsip syariah dalam hasanah card. Data dikumpulkan dengan metode field research (penelitian lapangan) dengan pendekatan hukum empiris. Hasil dari penelitian ini yaitu penerapan prinsip-prinsip syariah pada produk Hasanah Card oleh Bank Syariah Indonesia masih kurang sesuai dengan Fatwa DSN-MUI No. 54 Tahun 2006. Hal ini dapat dilihat dari fatwa DSN MUI mengenai ketentuan tadwidhdan ketentuan transaksi pada merchant non halal yang belum sepenuhnya sesuai dipraktikan dalam hasanah card.